Case report: Suspected plasmablastic lymphoma in a dog resembling the clinical presentation in humans - Giuliano, Antonio; Lam, Sin Yan; Flecher, Mayra C.; Horta, Rodrigo S. (Frontiers in Veterinary Science, 2023)
Plasmoblastic lymphoma is a rare form of lymphoma in people. PBL originates from plasmoblasts and usually present with a swelling/mass in the mouth/neck. A 7 year old Mongrel dog presented for a large oral and neck mass. Cytology and histopathology were suggestive of a round cell tumour with lymphoma being the most likley. An immunohistochemical (IHC) stains panel was performed and this showed positive CD 18 supporting the diagnosis of round cell tumour, but markers for T and B cell lymphoma, CD3, CD20 and PAX-5 were all negative. Other markers including cytokeratin AE1/3 (for epithelial cell origin), CD31 (for endothelial cells), SOX10 (for melanoma), IBa-1 (for histiocytic sarcoma) and CD117 (for mast cell tumour) were all negative. MUM1 (for plasma cells differentiation) was strongly positive and CD79a (B-cell and plasma cells) was also scantly positive. Based on the result of the histopathology and immunohistochemistry in combination with the clinical presentation, a suspected diagnosis of PBL was made. At the author knowledge this is the first case of highly suspected PBL in a dog.